Drazin Invertibility in a Certain Finite-Dimensional Algebra Generated by Two Idempotents. (25th October 2020) - Chen, Jianlong; Gao, Yuefeng; Li, Lifang
Abstract: In this article, we study the existence criterion and formulae of Drazin inverses of elements in a certain finite-dimensional algebra generated by two idempotents, under some prescribed conditions.